Thallium concentrations, sources and ecological risk in the surface sediments of the Yangtze Estuary and its adjacent east China marginal sea: A baseline study. (January 2019) - Zhuang, Wen; Liu, Yongxia; Tang, Lebin; Yue, Wen; Liu, Jinhu; Ren, Yuxuan; Wang, Xiping; Xu, Shanshan; Tai, Shaohua; Zhang, Jing; Zheng, Yu; Guo, Feng; et al.
Abstract: The distribution characteristics, sources and ecological risk of thallium (Tl) in the surface sediments of Yangtze Estuary and its adjacent sea were studied. Tl concentrations ranged from 0.369 to 1.197 μg g −1 with an average of 0.674 μg g −1, which was slightly higher than the corresponding background values. Tl concentrations were relatively high in sediments of the south bank of Chongming Island and the Hangzhou Bay mouth, and gradually decreased from inner shelf to outer seas. The variation trend of Tl concentrations was controlled by sediment characteristics, hydrodynamic conditions and sources together. The sediment flux of Tl in the study area was 428.6 t/yr. The Yangtze River, the Yellow River and atmospheric inputs of Tl accounted for 52.7%, 10.5%, and 0.15% of the total sediment flux, respectively. The result of potential ecological index indicated that Tl in surface sediments of the study area had no threat to the ecological environment. Highlights: More than 60% of Tl in surface sediment of the study area is contributed by rivers. The distribution characteristic of Tl is mainly controlled by ocean currents. On average >90% of Tl mass is from lithogenic materials. Tl could hardly cause any ecological hazard because of its low level.